CellularAutomataLib2: improving the support for cellular automata modelling in Modelica. Issue 3 (3rd May 2016) - Sanz, Victorino; Urquia, Alfonso; Leva, Alberto
ABSTRACT: CellularAutomataLib is a library developed by the authors to facilitate the description of Cellular Automata (CA) models in Modelica. It supports the description of 1D and 2D CA and their combination with other Modelica models. Modelling versatility and scalability are the main focus in the design. The internal behaviour of CA models is programmed in C, that is consequently hidden to the modelling tool and not considered in the causalization and manipulation of the model. A new version, named CellularAutomataLib2, is presented in this manuscript. The library has been extended to improve the simulation performance, by only evaluating active cells, and to support Lattice Gas Cellular Automata (LGCA) models. The library design and use are discussed. Two models, forest fire spread and the ARGESIM C17 'SIR-type Epidemic Spread', are used to illustrate the functionality of the library. CellularAutomataLib2 is freely available athttp://www.euclides.dia.uned.es (under the Modelica License 2).